The complementary Role of Indigenous Knowledge Systems in Landslide Disaster Management in Kanungu District, Uganda - Turyasingura, Benson; Ayiga, Natal; Benzougagh, Brahim; Kader, Shuraik; Kumar, Singh Sudhir; Nuwe, John BOSCO; Gweyi-Onyango, Joseph P.; Bojago, Elias (Kabale University, 2024)
This study aimed to investigate the use and effectiveness of Indigenous Knowledge Systems (IKS) in managing landslides in Kanungu District, Uganda. The study used the Likert scale and the multivariate probit (MVP) model and found that marginalization was a significant challenge facing local interventions in landslide disaster management. Factors such as farm size, credit availability, social group membership, access to extension services, farming experience, accessibility of weather and climatic information, and perception of climatic changes influenced the adoption of IKS, both positively and negatively. The study concludes that education programs should focus on farmer capacity building to mitigate landslide risks and emphasize the application of IKS in landslide hazard management.